2013
DOI: 10.1007/s13204-013-0264-3
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the optical property and photocatalytic activity of mixed phase nanocrystalline titania

Abstract: Mixed phase nanocrystalline titania are prepared by simple sol-gel method. The physico-chemical characteristics of the prepared nanoparticles are studied with X-ray diffraction, high-resolution transmission electron microscopy, RAMAN, BET, UV-Vis, steady state and time resolved photoluminescence. X-ray diffraction and Raman spectra clearly demarcate the anatase and rutile phase as both the phases give different diffraction patterns and Raman peaks. A comparison in the band gap indicates that pure anatase and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(50 citation statements)
references
References 43 publications
(28 reference statements)
6
41
0
3
Order By: Relevance
“…Generally, the values for all mixed-phase samples lies between these two values, and this lowering in the bandgap can be attributed to the presence of rutile, which induces additional states within the bandgap. The results shown here agree with those reported by other authors [35,36].…”
Section: Particle Size Estimationsupporting
confidence: 94%
“…Generally, the values for all mixed-phase samples lies between these two values, and this lowering in the bandgap can be attributed to the presence of rutile, which induces additional states within the bandgap. The results shown here agree with those reported by other authors [35,36].…”
Section: Particle Size Estimationsupporting
confidence: 94%
“…In general, a correlation was found between longer decay times of ∆abs in transient UV absorption/reflection measurements and higher activities. For example, time-resolved emission quenching studies comparing different forms of titanium dioxide found an average decay constant of 1.99 ns for anatase and 1.65 ns for the less active rutile phase [106]. Likewise, it was found that decorating titanium dioxide with Pt islands, acting as electron sinks, extended the life time of trapped holes from the picosecond to the millisecond time scale, in correlation with the observation of higher activity [107].…”
Section: Transient Phenomena In Tio 2 As a Tool For Understanding Itsmentioning
confidence: 87%
“…Hence, the charge transfer between the Ni 2? ions d-electron and TiO 2 conduction will appear (Paul and Choudhary 2014). The Ni 2?…”
Section: Drs Analysismentioning
confidence: 96%
“…The results obtained for the present studies are in correlation with this explanation already in the literature given (Aguilar et al 2013). The redshift of 0.2 mol% Ni-TiO 2 samples can be attributed to the charge transfer transitions between impurity band and the TiO 2 conduction band (Paul and Choudhary 2014). In TiO 2 , the valence band is composed of O-2p states and the conduction band is composed of Ti-3d states.…”
Section: Drs Analysismentioning
confidence: 99%